Pengembangan Sistem Kendali Mekanis Mobile Robot Menggunakan Roda Caster - Christiand; Jonathan (Cylinder : Jurnal Ilmiah Teknik Mesin, 2024)
A reliable control system is essential for the operation of a wheeled robot. A castor wheel is a robotic control device that enables the wheeled robot to navigate to various positions and orientations. One implementation method employs a servo motor to adjust the orientation of the castor wheel to a specific driving angle. The mechanism is robust, cost-effective, and simple to produce. This work demonstrates the development of a castor-wheel-based control mechanism utilizing a servo motor and the pure pursuit algorithm to determine the driving angle. The designated wheeled robot employs a BLDC motor as the primary actuator for its two main wheels. An experiment has been performed to assess the proposed control mechanism. The proposed control system achieved a position error of 0.228 m in the Y direction minimally and less than 1 m position error globally. This study presents mechanical, electrical, and software components.